Employment Effect of Innovation - d'Artis Kancs; Boriss Siliverstovs (Publications Office of the European Union, 2019)
We provide a novel evidence about the innovation-employment nexus by decomposing it by R&D intensity in a continuous setup and relaxing the linearity assumption. Using a large international firm-level panel data set for OECD countries and employing a flexible semi-parametric method – the generalised propensity score – allows us to recover the full functional relationship between the R&D-driven innovation and firm employment as well as address important econometric issues, which is not possible in the standard estimation approach used in the previous literature. Our results confirm that the relationship between innovation and employment entails important non-linearities responsible for significant differences in employment response to innovation at different R&D intensity levels.
Keywords: C14; C21; F23; J20; J23; O30; O32; O33; 330; R&D investment; employment; propensity score; firm-level data